Public Services of Muhammadiyah: The Theology of Al-Maun and the LAZISMU Zero Amil Rights - Nur Aida Ikrima; Mukhammad Ali Turdialiev Polatjon Ogli; Odilbek Khazratkulov; Clarizze Yvoine Mirielle; Arief Budiono; Kelik Wardiono (Jurnal Muhammadiyah Studies, 2024)
One of the core foundations of the movement of Muhammadiyah (Indonesia's second-largest Muslim organization) is the theological strength of the al-Ma’un Qur’anic chapter which was taught by Ahmad Dahlan, Muhammadiyah’s founder. Dahlan interpreted al-Ma’un into three main activities, namely education, health, and charity of the poor. He also transformed religious understanding from mere sacred doctrines that are socially "soundless" into a cooperation that frees human beings. In this modern era, there is a need to relive the spirit of al-Ma'un, especially in the condition of life that is full of social injustice. In doing so, Muhammadiyah established the Lazismu institution which functions to channel donation and zakat (almsgiving) funds. This paper aims to analyze the concept of social philanthropy in Lazismu’s independence in the effort to fulfill the al Maun theology so that all the collected zakat funds can be channeled for social services and how this independence concept grows the Muslim society's trust in Lazismu as a social philanthropy institution of Muhammadiyah. Method: This paper employed the qualitative normative research method. Results: This paper found that to achieve independence, Lazismu established businesses to cover the costs of zakat distribution worker's wages. Thus, the obtained zakat may be channeled without having it cut to pay for amil’s rights. In this case, the money is obtained from businesses (amal usaha), which are productive business units. A side effect of Lazismu’s independence is that the community's trust in this organization with experience an increase as it channels 100% of its zakat funds to other groups of beneficiaries and does not take any to wage the amil.